Improving Students’ Vocabulary Achievement Through Word Webbing Technique. - Irma Agustini; Yunita Agnes Sianipar (TRANSFORM : Journal of English Language Teaching and Learning, 2013)
ABSTRACT This study attempts to Improving Students’ Vocabulary achievement Trough Word Webbing Technique. The objective of the study is to discover whether the use of word webbing technique could significantly improving students’ vocabulary. This study conduct by applying Classroom Action Research which was carried out in two cycles in six meetings. The subject of this study of SMPN 4 Takengon, Aceh Tengah which consisted of 40 students. The quantitative data were collected by using observation sheet, questionnaire sheet and diary field. Based on the vocabulary test score, students’ score kept improving in every test. The mean of students’ score cycle (80) was higher than the fist cycle (67,75) and orientation test (55.25). based on observation sheet, questionnaire sheet and diary field, it was found that teaching learning process ran well. The students were more active and more enthusiastic during the teaching learning process in the second cycle than the first one. The result of the research showed that is use of word webbing technique significantly improving students’ vocabulary. Keywords : Word Webbing Technique, Action Research